1992
DOI: 10.1017/s0022112092000041
|View full text |Cite
|
Sign up to set email alerts
|

Lubricated pipelining: stability of core—annular flow. Part 5. Experiments and comparison with theory

Abstract: Results are given for experiments on water-lubricated pipelining of 6.01 P cylinder oil in a vertical apparatus in up- and downflow in regimes of modest flow rates, less than 3 ft/s. Measured values of the flow rates, holdup ratios, pressure gradients and flow types are presented and compared with theoretical predictions based on ideal laminar flow and on the predictions of the linear theory of stability. New flow types, not achieved in horizontal flows, are observed: bamboo waves in upflow and corkscrew waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
179
0
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(198 citation statements)
references
References 30 publications
16
179
0
3
Order By: Relevance
“…In pressure-driven two-layer/core-annular flows, several authors have conducted linear stability analyses by considering the fluids to be immiscible 4,[6][7][8] and miscible. 3,[9][10][11][12] This problem was also studied by many researchers experimentally 13,14 and numerically. [15][16][17][18] In miscible core-annular flows, the thickness of the more viscous fluid layer left on the pipe walls and the speed of the propagating "finger" were experimentally investigated by many authors [19][20][21][22][23] and the axisymmetric and "corkscrew" patterns were found.…”
Section: Introductionmentioning
confidence: 94%
“…In pressure-driven two-layer/core-annular flows, several authors have conducted linear stability analyses by considering the fluids to be immiscible 4,[6][7][8] and miscible. 3,[9][10][11][12] This problem was also studied by many researchers experimentally 13,14 and numerically. [15][16][17][18] In miscible core-annular flows, the thickness of the more viscous fluid layer left on the pipe walls and the speed of the propagating "finger" were experimentally investigated by many authors [19][20][21][22][23] and the axisymmetric and "corkscrew" patterns were found.…”
Section: Introductionmentioning
confidence: 94%
“…Subsequently, Hu and Joseph (1989) used the same method to compute the various energy terms for the disturbances with the maximum growth rates. Referring to the successful experiences with energy considerations of this kind by Boyd (1983, 1987), Hu and Joseph (1989), Kelly et al (1989), Chen et al (1990), Bai et al (1992), Dijkstra (1992) and Joseph and Renardy (1993), we may expect the above procedure to provide enough information to point out the physical characteristics of the various instabilities in two-phase flow.…”
Section: Introductionmentioning
confidence: 94%
“…These have included linear stability analyses for horizontal [6,7,[17][18][19] and vertical pipes [5,20], accounting for viscosity and density contrasts, experiments [21,22] and numerical simulations in straight [9,10,23] and corruagated pipes [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%